The Role of Yarn Bintik Paramita Small and Medium Industries on the Economic Growth of the Industrial Sector in Palangka Raya City - Rini Setyaningsih (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
The purpose of this study was to determine the role of Paramita Yarn Industry on economic growth in the Industrial Sector of Palangka Raya City and to determine the effect of Labor, Production Capacity and Production Value variables in the Palangka Raya Yarn Processing Industry on Economic Growth. This study uses multiple linear regression analysis techniques using IBM SPSS version 25. The type of data used is from this study primary data answers from business owners Benang Bintik Paramita. The results of this study indicate that the Paramita Spot Yarn Processing Industry has a fairly good role in Economic Growth. Labor, the level of production capacity has a partial and significant effect on economic growth and the value of production has no significant and negative effect on economic growth in the city of Palangka Raya. The results of this study are also labor, the level of production capacity has a simultaneous effect on economic growth.